SARS-CoV-2 Infection Among People Living With HIV Compared With People Without HIV: Survey Results From the MACS-WIHS Combined Cohort Study. (1st January 2022) - D'Souza, Gypsyamber; Tong, Weiqun; Gustafson, Deborah; Alcaide, Maria L.; Lahiri, Cecile D.; Sharma, Anjali; French, Audrey L.; Palella, Frank J.; Kempf, Mirjam-Colette; Mimiaga, Matthew J.; Ramirez, Catalina; Kassaye, Seble; et al.
Abstract : Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and coronavirus disease 2019 (COVID-19) symptoms among people living with HIV (PLWH) are not well described. Setting: Longitudinal survey within the MACS/WIHS Combined Cohort Study (MWCCS) of PLWH compared with similar HIV-seronegative (SN) individuals. Methods: Telephone-administered survey of MWCCS participants at 13 clinical research sites across the United States addressing COVID-19 symptoms, SARS-CoV-2 testing, and pandemic impact on social distancing and antiretroviral therapy (ART) use. Primary data collection occurred during May (wave 1), June–July (wave 2), and August–September, 2020 (wave 3). Results: One-third of MWCCS participants were tested for SARS-CoV-2 infection; 10% was tested ≥2 times. Similar proportions of PLWH and SN participants were tested, but SARS-CoV-2 positivity was higher among PLWH than among SN individuals (9.4% vs 4.8%, P = 0.003). Odds of SARS-CoV-2 positivity remained higher among PLWH after adjusting for age, sex, race/ethnicity, and study site (adjusted odds ratio = 2.0, 95% confidence interval = 1.2 to 3.2). SARS-CoV-2 positivity was not associated with CD4 cell counts among PLWH. Among SARS-CoV-2 positive participants, 9% had no symptoms, 7% had 1–2 mild symptoms, and 84% had ≥3 symptoms. Most of the (98%) participants reported physical distancing during all survey waves; self-reported ART adherence among PLWH was not adversely affected during the pandemic compared with the previous year (similar adherence in 89% of participants, improved in 9% of participants, and decreased in 2% of participants). Conclusions: Despite similar SARS-CoV-2 testing and physical distancing profiles by HIV serostatus among MWCCS participants, PLWH who reported SARS-CoV-2 testing were more likely to have a positive test result. Additional studies are needed to determine whether and why PLWH are at increased risk of SARS-CoV-2 infection. Abstract : Supplemental Digital Content is Available in the Text.